Adolf Reinach, Negative States of Affairs and the Concept of Omission - Woleński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
This paper examines Adolf Reinach’s views about negative states of affairs. The author briefly presents the history of the issue from the Middle Ages to the 20th century. The views of Reinach and Roman Ingarden are compared. A special focus is ascribed to the problem of omissions in the legal sense. According to the author, a proper solution to the problem of negative states of affairs locates negation at the level of language, not in reality.